A cultura psicológica no mercado de bensde saúde mental contemporâneo - Benelli, Sílvio José [UNESP] (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2009)
We studied the hypothesis of psychological culture proposed by Castel, 1987, by seeking to understand the current transformations in the social field and its occurrence in the areas of mental health (Psychiatry, Psychoanalysis, Psychology). The emergence of a new psychological cluster devoted to developing and improving the potential of the human being would aim towards the infinite programming of the human being, in the transition from a disciplinary society to one of control. With this perspective, psychology as a profession would be overcoming treatment and prevention, being redirected towards creating a relational sociability: Clinical Philosophy could be considered a therapeutic mode for normal people, and Enneagram and Neuro-Linguistic Programming as psychotherapeutic systems seeking to guide the human being towards global self-development. We decoded their strategic function, while they were situated in the broader context of the current form of risk management in the administration of problematic populations.

Estudou-se a hipótese da cultura psicológica proposta por Castel em 1987, buscando compreender as atuais transformações no campo social e suas incidências nas áreas da saúde mental (psiquiatria, psicanálise, psicologia). O surgimento de um novo arquipélago psicológico voltado para o desenvolvimento e o aprimoramento do potencial humano visaria a uma programação infinita do ser humano na transição da sociedade disciplinar para uma sociedade de controle. Nesse panorama, a psicologia como profissão estaria superando o tratamento e a prevenção, dirigindo-se para a criação de uma sociabilidade relacional; a filosofia clínica poderia ser considerada uma modalidade terapêutica para pessoas normais, e o eneagrama e a programação neurolinguística seriam sistemas psicoterapêuticos que buscam levar o ser humano a um autodesenvolvimento global. Decifrou-se sua função estratégica quando foram situados no contexto mais amplo da atual forma de gestão dos riscos na administração de populações problemáticas.
The psychological culture in the contemporary mental health marketplace
Keywords: Philosophy; Neuro-Linguistic Programming; Social Psychology; Filosofia; Programação neurolinguística; Psicologia social